Effect of Fiber Volume Fraction and Water Absorption toward Bending Strength of Coconut Filters/ Polyester Composite - I Putu Lokantara; Ngakan Putu Gede Suardana; I Made Gatot Karohika (Department of Mechanical Engineering, University of Udayana, 2009)
The variation of fibre volume and the duration of water soaking take influence on the mechanical properties of composite. This research aim is to know the influence of fraction volume fibre and soaking duration on the mineral watertoward the tensile strength and flexural of polyester-coconut-tapis composite. This research used coconut-tapis fibre which is cut 1 cm in length with 0%, 5%, 7,5%, and 10% fiber volume fraction, unsaturated-polyester (UPRs) matrix resin type Yucalac 157 BQTN-EX, and MEKPO hardener. The flexure specimen are made by press hand lay-up method and cut according ASTM D790-03 for the flexure test. The result of flexure test shows that the duration of soaking and the fiber volume fraction give a significant effect on the flexural strength of composite. The highest strength are reached by composite with 10% fibre volume on 48 hour soaking time equal to 41.994 MPa. The flexure modulus happenend shows increasing until 24 hour soaking time. The highest modulus are reached by composite with 10% fibre volume equal to 7.114 GPa while the lowest are reached by composite with 0% fibre volume equal to 3,023 GPa.